Human Capital, Urbanization, and Canadian Provincial Growth - Coulombe, Serge (Université d'Ottawa | University of Ottawa, 2001)
This paper investigates the conditional convergence of both human capital indicators and nominal per capita income across Canadian provinces in a panel-data empirical framework. Long-run relative provincial steady states are determined by relative rates of urbanization, one-time shocks to Quebec’s and Alberta’s relative steady states, and a Nova Scotia fixed effect. Indicators of relative human capital ratios appear to have converged following a pattern that is common and similar to per capita income but with two notable exceptions. First, in Alberta, the 1973 oil shock contributed to the rise in per capita income but its effect on human capital is significant only for females. Second, human capital appears to remain concentrated in the relatively poor province of Nova Scotia. Two notable findings come out of the analysis. First, nominal income disparities at the provincial level appear to be real, not just nominal. Second, the analysis suggests that at the regional level, human capital is a necessary but not sufficient condition for being wealthier in the long run.
Keywords: convergence; urbanization; regional growth; human capital; Canadian regions; neo-classical growth model